Student excellence awards and white coat ceremony RX 24 - Ahmad Kamal, Syahida Fathiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2025)
The Student Excellence Awards segment aimed to recognise students who have excelled academically and demonstrated commendable dedication throughout their studies during the March - August 2025 semester. The presentation of awards not only celebrated individual achievements but also highlighted the collective efforts of students, academic staff, mentors, and families in supporting students’ success. This recognition served as a source of motivation for other students to continuously improve their performance and uphold high academic standards.